Angioscopic assessments and clinical outcomes one year after polymer-free biolimus A9-coated coronary stent implantation. Issue 5 (May 2021) - Tsujimura, Takuya; Ishihara, Takayuki; Okuno, Shota; Iida, Osamu; Kurata, Naoya; Asai, Mitsutoshi; Masuda, Masaharu; Okamoto, Shin; Nanto, Kiyonori; Kanda, Takashi; Matsuda, Yasuhiro; Hata, Yosuke; et al.
Highlights: The polymer-free biolimus A9-coated coronary stent (DCS) has novel features. One-year angioscopic and clinical outcomes were compared between DCS and durable-polymer drug-eluting stent (DP-DES). Incidence of thrombus adhesion was similar in DCS and DP-DES groups. The cumulative incidence of target lesion revascularization was similar for DCS and DP-DES. DCS can be used with similar safety and efficacy as DP-DES in the clinical setting. Abstract: Background: Polymer-free biolimus A9-coated coronary stent (DCS) has novel features which lead to the expectation of better arterial healing. However, comparisons of intravascular status between DCS and drug-eluting stents (DES), and robust real-word clinical assessments of DCS have been lacking to date. Methods: From September 2017 to September 2018, we evaluated the intra-vascular status of 74 DCS implanted in 55 lesions from 43 patients using coronary angioscopy (CAS) approximately one year after implantation from a cohort of 219 lesions in 158 patients. We set 239 second-generation durable-polymer DES (DP-DES) implanted in 211 lesions from 180 patients from a cohort of 2652 lesions in 1914 patients as the control. Angioscopic images were analyzed to determine (1) the dominant degree of neointimal coverage (NIC) over the stent; (2) the heterogeneity of NIC; (3) yellow color grade of the stented segment; and (4) the presence of intra-stent thrombus. The primary outcome was the incidence of thrombus and secondary outcomes were the other CAS findings, and the 1-year clinical outcomes which included target lesion revascularization (TLR) and major adverse cardiac events (MACE). To minimize inter-group differences in baseline characteristics, propensity score matching was performed for clinical outcomes. Results: Incidence of thrombus adhesion was similar in DCS and DP-DES groups (28.4% versus 22.6%, p = 0.31). However, the dominant NIC grade was significantly higher in DCS ( p < 0.001), while NIC was more heterogeneous in DCS than in DP-DES ( p = 0.001). Maximum yellow color grade was similar ( p = 0.22). After propensity score matching, 202 lesion pairs from 146 patient pairs were retained for analysis. The cumulative incidence of TLR (4.6% versus 3.8%, p = 0.38) and MACE (11.6% versus 11.7%, p = 0.84) was similar for DCS and DP-DES. Conclusions: DCS showed thrombus adhesion and clinical outcomes at 1 year similar to DP-DES. DCS can thus be used with similar safety and efficacy as DP-DES.